Nghiên cứu sự tạo phức của lantan với L-methionin - Uyển và cộng sự, Nguyễn Trọng (Vietnam Journal of Chemistry, 2014)
The composition and stability complex between lanthanum and L.methionine have been studied by pH-meter titration method at the temperature of 20, 30, 40, 50±1oC and ionic strenght of 0.1 (KNO3) solution. The first stability constand of this comlex has been ealculated. This complex has been isolated ion solid state. The structure of the complex was determined by thermal composition and IR spectral methods.